2016
DOI: 10.4103/0972-6748.196049
|View full text |Cite
|
Sign up to set email alerts
|

Self-injurious behavior, emotion regulation, and attachment styles among college students in India

Abstract: Context:Intentional self-directed acts of injury are the most common among adolescents and young adults. Developmental psychopathology theories that conceptualize pathways to self-injurious behaviors (SIBs) implicate insecure attachment representations and inadequate self-regulatory skills to cope with emotional distress.Aims:The study aimed to examine relationships between SIBs, attachment, and emotion regulation among college students.Materials and Methods:A total of 470 participants from undergraduate and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…The results of the present study indicated a negative, direct correlation between attachment styles and difficulties in emotion regulation. In this respect, our findings are in line with the results of previous studies (9,14,17). Many individuals could easily deal with stress due to proper emotional relations with their parents during adolescence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study indicated a negative, direct correlation between attachment styles and difficulties in emotion regulation. In this respect, our findings are in line with the results of previous studies (9,14,17). Many individuals could easily deal with stress due to proper emotional relations with their parents during adolescence.…”
Section: Discussionsupporting
confidence: 92%
“…Studies show that attachment styles (9) and initial stressful events (10) increase the frequency and intensity of non-suicidal self-injury (NSSI) through disrupting the emotion regulation process. In the early years of life, children establish a relatively stable emotional bond with and feel safe around those they interact with.…”
Section: Introductionmentioning
confidence: 99%
“…While the recent trends seemed to be toward higher NSSI rates as shown in a sample of community college students, where NSSI was noted in about 31% of the students, similar objections may be raised for this study as well, as 15% of these students endorsed clear suicidal intent at the time of the self-injurious act. While NSSI generally does not involve planning and/or intending to complete a suicide attempt, in this study, 18% of the subjects were assessed as having planned a suicide attempt (Kharsati & Bhola, 2016). Even in children, a suicide attempt may be falsely categorized as DSH.…”
Section: Prevalencementioning
confidence: 79%
“…Adverse experiences during childhood can hinder the development of a secure attachment style which can impact upon subsequent relationships [ 27 , 28 ] and lead to difficulties in regulating emotional responses [ 29 ]. Indeed, those in the repeat self-harm group scored lower than those in the first episode group on an established measure of attachment that assessed the extent to which respondents felt secure in their relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Abuse and neglect in childhood are associated with the development of maladaptive attachment styles [ 26 ]. In turn, insecure attachment styles are often associated with deficits in regulating emotional responses and use of maladaptive emotional regulation behaviours including self-harm [ 27 , 28 ]. Indeed, studies with adolescents who have experienced ACEs have found that NSSI is often employed as a means of emotion regulation [ 29 ].…”
Section: Introductionmentioning
confidence: 99%